Genomic analysis made easy (Game V1): An automated software for plant genome assembly and annotation from illumina sequencing - Ali, Mohammad Ajmal; Mahato, Rajesh; Lee , Joongku (Bangladesh Journal of Plant Taxonomy, 2024)
The recent development and affordable accessibility of the next-generation high-throughput sequencing technology and artificial intelligence have propelled more researchers to get involved in genomics and to the threshold of a new beginning in understanding, utilizing, and conserving the biodiversity. However, one of the biggest challenges for the analysis of high-throughput sequencing reads is the whole genome assembly and annotation. Availability of user-friendly free software that manages all types of sequenced DNA to be used in a local environment is lacking. Hence, the Genomic Analysis Made Easy (GAME v1) software has been developed using Python to provide a user-friendly, fast, free, and automated GUI-based solution for plant genome assembly and annotation. The software performs on a Linux-based operating environment with a minimum of 16 GB RAM and 100 GB disc space, fully automated from the installation to execution, thus requiring minimal bioinformatics expertise for the execution. The GAME v1 generates detailed quality reports of the raw reads, GenomeScope heterozygosity report, QUAST contigs and scaffolds results, BUSCO summary plot, COG functional annotation chart, GO chart, NCBI and UniProt annotations, KEGG pathway distribution graph, and RepeatMasker plots. The nuclear genome of Chenopodium pallidicaule retrieved from NCBI was assembled and annotated successfully using GAME v1, revealing preliminary genome size estimate of around 419.54 Mb based on GenomeScope analysis prior to assembly. The final assembly, as assessed by QUAST, unveiled a total length of 285.85 Mb (0.29 Gb) containing 23,806 genes. This automated solution will facilitate plant genomics research by revealing the underlying insights of draft nuclear genomes. The software is available at https://arraygen.com/game Bangladesh J. Plant Taxon. 31(2): 225-238, 2024 (December)